Melhoramento de feijão preto para resistência à murcha de fusário: identificação de marcadores moleculares e seleção de populações segregantes e linhagens - Torres, Mário Henrique Rodrigues Mendes (2020)
Fusarium wilt, caused by the fungus (Fusarium oxysporum f. sp. phaseoli) is one of the most important diseases affecting bean culture (Phaseolus vulgaris L.). Among the methods of controlling this disease, genetic resistance is the most efficient. However, there is little information on the genetics of the fusarium wilt reaction (FOP). Three studies were carried out with the objectives of: i) selecting promising parents and the segregating populations for reaction to fusarium wilt, grain productivity and 100 grain mass; ii) estimate genetic parameters and select breeding lines resistant to fusarium wilt, with high productivity and greater mass of 100 grains; iii) check if there is a genetic relationship between these traits; iv) study genetic control and identify SNP molecular markers linked to QTLs for reaction to fusarium wilt in the bean cultivar BRS FP403. In the first study, 25 segregating populations obtained from crosses in the partial diallel scheme between two groups of the five parents were evaluated: group I with breeding lines resistant to fusarium wilt and group II with susceptible breeding lines, but with superior agronomic characteristics. The populations were evaluated in Santo Antônio de Goiás-GO in an area with natural infestation of the pathogen, in the winter / 2016 (generation F2), winter / 2017 (generation F3) and winter / 2018 (generation F4). The evaluated traits were the reaction to fusarium wilt, productivity and mass of 100 grains. Significant differences between populations were detected for all traits. The joint diallel analysis showed the existence of additive and non-additive effects, with a predominance of additive effects, for the three traits studied. The gi estimates revealed that the parents BRS Esplendor (-0.13) and CNFP 15207 (-0.76) are indicated to form populations with greater resistance to fusarium wilt. The CNFP breeding lines 15194 is indicated to form populations with greater resistance to fusarium wilt (-0.59) and greater mass of 100 grains (0.69). The cultivar BRS FP403 is indicated as the parents for increasing productivity (218) and mass of 100 grains (1.46). Among the susceptible parents, CNFP 11995 stood out for forming populations with high productivity and a mass of 100 grains, simultaneously. The populations BRS FP403 / CNFP 11995, CNFP 15194 / CNFP 11995 and CNFP 15194 / CNFP 11976 are the most promising for the extraction of superior breeding lines for the three traits simultaneously. In the second study, breeding lines from two populations were evaluated (BRS Esplendor / BRS Expedito and BRS Expedito / CNFP 15867), selected for their high resistance to fusarium wilt, high productivity and greater mass of 100 grains. Two experiments were conducted in the winter crops of 2015 and 2016, in Santo António de Goiás-GO, with 116 breeding lines from these two populations and five witnesses in a triple 11x11 latex experimental design, in an area infested with the pathogen. Reaction to fusarium wilt, yield and mass of 100 grains were evaluated. Analysis of variance and estimated genetic parameters were performed. Differences between lineages were identified in all environments for all traits. The estimates of heritability and expected gain with direct selection indicated the possibility of obtaining genetic gains for each traits in isolation. In the simultaneous selection of the breeding lines for the four traits, based on the joint analysis, the expected gains with the selection of the 31 best breeding lines were 22.1% for reaction to fusarium wilt, 6.6% for productivity and 7.7% for mass of 100 grains. Five breeding lines have high potential to be indicated as new cultivars, as they showed resistance to fusarium wilt, high productivity and a mass of 100 grains, being superior to the cultivars available on the market today. In the third study, genotyping of SNPs and SilicoDArT markers was performed using the DArTseq technology of a population mapping in the F2 generation obtained from the crossing between the cultivars BRS FP403 (resistant) x BRS Horizonte (susceptible). 165 progenies were obtained and evaluated in generations F2: 4 and F2:5, together with four controls. The experiments were installed in a 13x13 triple lattice design, in an area infested with the pathogen, in the winter/2016 (F2:4) and winter/2017 (F2:5) harvest in Santo Antônio de Goiás - GO. Evaluation of the reaction to fusarium wilt was performed. A genetic map was obtained comprising 702 markers with a total length of 3069 cM and an average distance between marks of 4.9 cM. The analysis of phenotypic data showed the presence of variability between the progenies and the possibility of success with the selection, with high estimates of genetic variance, heritability (90%) and expected gain with the selection (37%). Considering the two years and the joint analysis, 6 different QTLs were identified associated with the reaction to the fusarium wilt and there was an interaction between the QTLs and the years. Based on the joint analysis, four QTLs were identified on chromosomes 1, 2, 3 and 4, explaining from 5.8 to 40.5% of the variation, indicating that the inheritance of the reaction to fusarium wilt is complex. The QTL FOP2.3403H stood out for explaining the greater proportion of the phenotypic variation (40.5%) and being stable in the different years. The QTL FOP3.2403H explained 6.3% of the phenotypic variation and was also stable over the years. These markers have great potential for use in assisted selection.